Influence of maternal periuterine and periovarian fat on reproductive performance and fetal growth in rats - Gomes, Maria Eduarda P. [UNESP]; Didomizio, Luigi M.J. [UNESP]; Sinzato, Yuri K. [UNESP]; Paula, Verônyca G. [UNESP]; Souza, Maysa R. [UNESP]; Gallego, Franciane Q. [UNESP]; Barco, Vinícius S. [UNESP]; Volpato, Gustavo T.; Damasceno, Débora Cristina [UNESP] (FapUNIFESP (SciELO), 2023)
We aimed to evaluate how high-fat diet consumption can interfere with rat reproductive performance and fetal development. High-fat diet (HFD) was initiated in 30-day-old rats, distributed into two groups (n=7 animals/group): Rats receiving a standard diet and rats receiving HFD. At adulthood, the rats were mated, and on day 21 of pregnancy, the females were anesthetized, decapitated, and submitted to laparotomy to obtain visceral and periovarian adipose tissue. The uterine horns were exposed for analysis of maternal reproductive performance. The fetuses and placentas were weighed and analyzed. Pearson’s correlation test was used, and p<0.05 was considered significant. There was a significant positive correlation (HFD consumption x increased periovarian fat) and a negative correlation with the implantation, live fetus numbers and lower litter weight. Furthermore, the increased relative weight of periuterine fat was related to the lower number of live fetuses and litter weight. Regarding the fetal weight classification, there was a negative correlation between the relative weight of periovarian fat and the percentage of fetuses appropriate for gestational age and large for gestational age. Therefore, our findings show that HFD maternal intake negatively influenced on reproductive performance and fetal growth.
Keywords: fetus; High-fat diet; pregnancy; rats; reproduction